Analysis of scheduling models applicable in referral health systems - Agola, Joshua; Raburu, George (My University, 2018)
Scheduling patient referrals is one of the most important administrative responsibilities performed in the medical office. A referral scheduling algorithm can be a useful tool in the hands of a primary provider. Primary providers are lacking knowledge regarding the care and treatment of chronic diseases and are not familiar with the current status of available resources (consultant doctors) for patient referrals. During patient referral there is a need to know of the availability of the consultant doctor and his/her status in terms of the patient workload. Referring a patient to a doctor with many patients on the waiting queue might delay the treatment. This can results in “added healing time, pain, and even death. This paper investigates the scheduling models applicable in referral health systems and hence proposes a suitable scheduling optimization model.
Keywords: Dynamic; Static; Scheduling; Referral; Model